The Effect of Computer-assisted Language Learning (CALL) on Immediate and Delayed Retention of Vocabularies in General English Course - Sedaghatkar, Mozhgan (International journal of applied linguistics & English literature, 2018)
Vocabulary learning is essential for language acquisition; however, it is considered problematic for the second language learners. As a teacher of General English Course, I witness majority of students state that "It’s difficult for me to remember long words", "I rapidly forget new words", "I frequently repeat words", etc. As a matter of fact, learning vocabulary is one of the most boring tasks that language learners face with. Hence, different ways have been tried towards making vocabulary learning easier. In this regard, recent years have shown an interest in using computers for foreign language teaching and learning. A previous decade, the use of computers in the language classroom was of concern only to a small number of specialists. However, with the introduction of multimedia computing and the Internet, the role of computers in language teaching has now become a key issue that great numbers of language teachers throughout the world face with. In this regard, the present study sought to investigate the effect of computer assisted language learning (CALL) on immediate and delayed retention of vocabularies among Iranian university students in General English Course. In this regard, 58 students from Payam Noor University of Aradan and Garmsar, Iran, were selected at random on the basis of Nelson test and then were divided into experimental and control groups each one including 29 students. A vocabulary test (as a pretest) was administered to the subjects in both groups. The goal was to check what words were unknown to the subjects in both groups. After the administration of the vocabulary test, about 21 words out of 114 new words were omitted since these words were known to the subjects in both groups. During the study, the researcher taught each group in 3 sessions (each session 90 minutes). After completion of each session, both groups were assessed through an immediate posttest. The subjects were also assessed for delayed posttest one month after teaching sessions (posttest 2). The results obtained throughout the study indicated that there was a significant difference between CALL users and nonusers in favor of the experimental group (p<0.05). It was also concluded that the university students had a positive attitude toward using CALL for learning vocabulary. In light of the findings of the study, the effectiveness of CALL on immediate and delayed retention of vocabularies was approved.